'ALSO MEIN ALLERLIEBSTER REDETTE IHRE SAPHO MIT DEM KRIEGE': LITERARY ROLE‐PLAY IN THE WAR POETRY OF ANNA LOUISA KARSCH. (9th June 2016) - Pilsworth, Ellen
ABSTRACT: Anna Louisa Karsch stylised herself as an uneducated peasant poet possessing natural genius, moved by her ʻfeminineʼ passions and ignorant of literary conventions. As a result of her successful self‐presentation, until recently scholars have not fully grasped the ways in which she engaged in literary role‐play in her poems – instead often reading her works autobiographically or as statements of authentic personal feeling. By demonstrating some of the contradicting viewpoints her poems express on the topic of the ongoing Seven Yearsʼ War, this article should prove two things. Firstly, that Karsch was acutely aware of poetic techniques and genre conventions, employing and citing a variety of literary traditions; and secondly, that by playing different literary roles in her poems, making use of classical, biblical and popular genres, she approaches the topic of war from a variety of perspectives that cannot be reduced to one of simple patriotism, as has been done by most Karsch scholars since her lifetime. In short, I argue that the ʻvoicesʼ in her poems should not be automatically conflated with the authorʼs own. Die schlesische Bäuerin Anna Louisa Karsch hat sich als ungebildetes ʻweiblichesʼ Naturgenie präsentiert, das seine dichterische Inspiration der Natur und den Siegen Friedrichs des Großen verdankte. Infolge dieser höchst erfolgreichen Selbstpräsentation ist Karsch von der Wissenschaft lange Zeit unterschätzt worden. Ihre mannigfaltigen literarischen Rollenspiele und Selbstinszenierungen sind bisher kaum erforscht worden. Stattdessen werden ihre Gedichte oft reduktiv als Autobiographie verstanden. In diesem Artikel soll im Gegenteil belegt werden, wie sie literarische Konventionen aus der Klassik, der Bibel und dem populären Kriegsdiskurs verwendete, um völlig unterschiedliche Meinungen zum aktuellen Thema des Siebenjährigen Krieges auszudrücken. Wie in der Untersuchung gezeigt wird, resultieren diese verschiedenen Meinungen oft aus der literarischen Rolle, die gerade gespielt wird, und können nicht als ʻauthentischeʼ Ansichten der Autorin selbst gelten, auch wenn sie so inszeniert werden.